Study of Vulnerability Aspects of Beef Cattle Farming Business - Amam Amam; Bambang Hidayat Setyawan; Mohammad Wildan Jadmiko; Pradiptya Ayu Harsita; Supardi Rusdiana; Muchamad Luthfi (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2021)
Farmer accessibility to resources plays an essential role in developing livestock farming businesses, but the vulnerability aspect is one of the obstacles for farmers' accessibility to resources. This research aims to examine aspects of the vulnerability of beef cattle farming businesses and analyze their effects on the accessibility of farmers to resources. The research was conducted from May to September 2019 in Purnama Village, Bondowoso District. Purnama Village is one of the villages developed by the University of Jember to develop a beef cattle farming business in the Bondowoso District. Respondents were all 201 beef cattle farmers in Purnama Village. The research variables consist of aspects of the vulnerability of the beef cattle farming business (X), financial resources (Y1), technological resources (Y2), and physical resources (Y3). Data were obtained using the FGD (Focus Group Discussion), observation, and survey methods. The survey was conducted using interviews and questionnaires. Data were analyzed using the PLS (Partial Least Square) method. The results showed that the vulnerability of the beef cattle farming business had a negative and significant effect on the accessibility of farmers to financial and physical resources and a negative but not significant effect on technological resources. The conclusion of the research shows that the vulnerability of the beef cattle farming business had a negative impact on the livestock farming business resources, so it needs to get special attention from stakeholders.